Perbedaan asupan makan balita di perkotaan dan perdesaan pada provinsi dengan beban gizi ganda - Puji Lestari; Susetyowati Susetyowati; Mei Neni Sitaresmi (Jurnal Gizi Klinik Indonesia, 2020)
Differences in food intake among children under five years in urban and rural areas in provinces with the double burden of malnutritionBackground: The double burden of malnutrition is one of the nutritional problems in children at national and global levels. Food intake is the main cause of the double burden of malnutrition. Differences in residence in urban and rural areas will affect food access which will have an impact on different food intake. Objective: To analyze the differences in energy, protein, fat, and carbohydrate intake of children under-fives in urban and rural areas in provinces with the double burden of malnutrition. Methods: This research used secondary data analysis using the Total Diet Study (TDS) 2014. The subjects of this study were 813 children in provinces with a dual burden of malnutrition that fulfilled the inclusion and exclusion criteria. Provinces with the double burden of malnutrition are provinces with a prevalence of underweight children aged ≥24-59 months at >22.36% and a prevalence of overweight children age ≥24-59 months at >1.23%. Total Diet Study (TDS) data will provide information on food intake of children through recall results, differences in residence obtained from district classification data, the double burden of malnutrition data obtained from children nutritional status is overweight and underweight based on weight and age data of children processed using WHO-ANTRO software. Results: The average intake of energy, protein, and fat in the urban area are higher than in a rural area, but the average carbohydrate intake in an urban area is lower than in a rural area. The average intake of energy in urban was 1300.01 kcal, in rural areas was 1223.23 kcal (p=0.0008). The average intake of protein in urban was 55.03 g, in rural areas was 47.67 g (p<0.0001). The average intake of fat in urban was 47.99 g, in rural areas was 37.12 g (p<0.0001). The average intakes of carbohydrate in urban were 163.61 g, in rural areas was 178.88 g (p=0.0042).Conclusions: There are differences in energy, protein, fat, and carbohydrate intake of children under five years in urban and rural areas in provinces with the double burden of malnutrition.